Dataset of metazoan identification using 18s rRNA eDNA metabarcoding from seawater at Hybrid-Ocean Thermal Energy Conversion (H-OTEC) site of Peninsular Malaysia - Eziwar Dyari, Herryawan Ryadi; Muhammad Rasib, Muhammad Adam; Abu Bakar, Jaafar; Suriyanti, Su Nyun Pau (Data in brief, 2025)
Environmental DNA (eDNA) is a very useful method for studying the biodiversity as it obtains genetic materials from environmental samples such as soil, water and air. This highly sensitive detection could attain information despite the scarcity of population densities. This non-invasive approach is feasible particularly in impact assessment of marine development. Hybrid Ocean Thermal Energy Conversion (H-OTEC) is a renewable energy technology that generates electricity by using sea water temperature differentials. While the H-OTEC is currently in its pre-commissioning state, it is crucial to provide a baseline data on the marine biota in this site. This study targets the 18s rRNA genes of the marine metazoans at the H-OTEC plant site at Port Dickson, Negeri Sembilan, Malaysia. Ten litres of seawater were collected from the site and immediately filtered through a 0.2 µm cellulose membrane filter. The eDNA extraction was carried out using cetyltrimethylammonium bromide (CTAB) protocol and sent for next generation sequencing. High-throughput sequencing using the Illumina platform produced 113,980 filtered reads, corresponding to 73 genera, 64 families, and 6 phyla of marine metazoans in the area under examination. The highest relative abundance belongs to the phylum Arthropoda (85%), family Paracalanidae (45%) and genus Bestiolina (38%). The diversity indices indicate a great deal of biodiversity in the ecosystem.